Interaction Between Local Culture, Financial Technology, and MSME Performance: A Systematic Literature Review - Karim, Kurniati; Kamaludin, Kamaludin; Indriani, Rini; Husaini⁴, Husaini⁴ (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a crucial role in the national economy, especially in developing countries like Indonesia. MSMEs not only contribute to GDP but also absorb a large number of workers (Ministry of Cooperatives and SMEs, 2023). In the context of globalization and digitalization, financial technology (fintech) is a new driver for MSMEs to increase access to financial services. However, the adoption of fintech cannot be separated from the local cultural context that influences the behavior, beliefs, and preferences of MSME actors. Therefore, it is important to understand the interaction between local culture, financial technology, and MSME performance. This study was conducted using a systematic literature review method with the PRISMA approach. The identification process was carried out through the Google Scholar, Scopus, and ScienceDirect databases with the keywords: